Evaluating watershed management projects - Kerr, John M.; Chung, Kimberly (International Food Policy Research Institute, 2001)
Watershed projects play an increasingly important role in managing soil and water resources throughout the world. Research is needed to ensure that new projects draw upon lessons from their predecessors' experiences. However, the technical and social complexities of watershed projects make evaluation difficult. Quantitative and qualitative evaluation methods, which traditionally have been used separately, both have strengths and weaknesses. Combining them can make evaluation more effective, particularly when constraints to study design exist. This paper presents mixed-methods approaches for evaluating watershed projects. A recent evaluation in India provides illustrations.